2004
DOI: 10.1161/01.res.0000121103.03275.ec
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase/Akt Regulates Angiotensin II–Induced Inhibition of Apoptosis in Microvascular Endothelial Cells by Governing Survivin Expression and Suppression of Caspase-3 Activity

Abstract: Abstract-Angiotensin II (Ang II) plays essential roles in vascular homeostasis, neointimal formation, and postinfarct remodeling. Although Ang II has been shown to regulate apoptosis in cardiomyocytes and vascular smooth muscle cells, its role in vascular endothelial cells (ECs) remains elusive. To address this issue, we first performed TUNEL and caspase-3 activity assays with porcine microvascular ECs challenged by serum deprivation. Ang II significantly reduced the ratio of apoptotic cells and caspase-3 acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 40 publications
1
64
0
2
Order By: Relevance
“…Salt intake is one important physiological factor that regulates renin secretion and consequently ANG II levels. Our data support a recent study (35) that indicates that ANG II plays a critical antiapoptotic role in vascular endothelial cells by interfering with mechanisms involving phosphatidylinositol 3-kinase (PI3-kinase)/Akt activation and survival pathways.…”
Section: Discussionsupporting
confidence: 92%
“…Salt intake is one important physiological factor that regulates renin secretion and consequently ANG II levels. Our data support a recent study (35) that indicates that ANG II plays a critical antiapoptotic role in vascular endothelial cells by interfering with mechanisms involving phosphatidylinositol 3-kinase (PI3-kinase)/Akt activation and survival pathways.…”
Section: Discussionsupporting
confidence: 92%
“…Second, AngII inhibits apoptosis of EPCs under serum starvation conditions, which may help maintain the number of EPCs when they are recruited to ischemic regions. We further investigated the mechanisms underlying this effect by examining the PI3-kinase/Akt pathway, which lies downstream of AT1R [6]. It was found that the pathway also plays an essential role in the AngII-induced antiapoptotic signaling of EPCs.…”
Section: Discussionmentioning
confidence: 99%
“…AngII inhibits EC apoptosis [6], upregulates adhesion molecules [7] and potently augments endothelial nitric oxide synthase (eNOS) mRNA expression, which thereby increases nitric oxide (NO) release [8]. Therefore, we propose that AngII may have similar effects on EPCs as well.…”
Section: Introductionmentioning
confidence: 95%
“…Survivin disruption abrogates the effects induced by angiogenic factors (25), pointing to survivin as a key factor for endothelial cell integrity. Similarly, angiotensin II enhances survival of retinal endothelial cells, which is mediated by up-regulation of survivin through the phosphatidylinositol 3-kinase/Akt pathway and inhibits hyperoxygen-induced retinal regression through survivin in a murine model (66). Apoptosis in human umbilical vascular endothelial cells (HUVEC) is inhibited by angiopoeitin 1 via up-regulation of survivin expression through the forkhead-related transcription factor pathway (67).…”
Section: Role Of Survivin and Cytokine-regulated Expression In Vasculmentioning
confidence: 99%